2022
DOI: 10.1021/acs.jmedchem.1c01572
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Regulated Cell Death with Pharmacological Small Molecules: An Update on Autophagy-Dependent Cell Death, Ferroptosis, and Necroptosis in Cancer

Abstract: Regulated cell death is a widely attractive subject among the topics of cancer therapy and has gained some advances for discovery of targeted anticancer drugs. In the past decade, nonapoptotic regulated cell death has been implicated in the development and therapeutic responses of a variety of human cancers. Hitherto, targeting autophagy-dependent cell death (ADCD), ferroptosis, and necroptosis with small molecules has been emerging as a hopeful strategy for the improvement of potential cancer therapy, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Accumulating evidence has revealed that necroptosis genes play an important role in cancer initiation and progression ( 9 , 10 ). Necroptosis genes are also involved in tumorigenesis, distant metastasis and immunosuppression ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has revealed that necroptosis genes play an important role in cancer initiation and progression ( 9 , 10 ). Necroptosis genes are also involved in tumorigenesis, distant metastasis and immunosuppression ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, small molecules, including Imatinib, Bexarotene, Midostaurin, FH535, CGP.082996, CMK, PF.4708671, JW.7.52.1, KIN001.135 and Z.LLNle.CHO also had more significant benefits in high-risk patients. Recent research confirmed that targeting necroptosis with small molecules is a promising strategy for cancer therapy, which may be the key to overcoming apoptosis resistance, and has advantages in overcoming apoptosis resistance and stimulating antitumor immunity (36). Therefore, we believe that the NRGscore can help identify better treatment strategies for individual patients with advanced BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, small molecules, including imatinib, bexarotene, and midostaurin, FH535, CGP.082996, CMK, PF.4708671, JW.7.52.1, KIN001.135, and Z. LLNle.CHO also had more significant benefits in high-risk patients. Recent research confirmed that targeting necroptosis with small molecules is a promising strategy for cancer therapy, which may be the key for overcoming apoptosis resistance, and has advantages in overcoming apoptosis resistance and stimulating antitumor immunity ( Wu J. et al, 2022 ). Therefore, we believe that the NRG score can help identify better treatment strategies for individual patients with advanced BLCA.…”
Section: Discussionmentioning
confidence: 99%